(3CbQGHGRjfs - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3UaI eYLhf GdHGQOg ef GdHdZe hGdShOGA ai GdeaGUd hGdYUH s
(3BNQgG (B:s
(3fGaY ddeYOI RGFO ai GdLeGY hbQfad hLhQjhG hRfLHjd hadad hjMQc MJi jNJdW Ke jUYH Ydi QNGeg s
(3fSNJ ef fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B136s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdWHs